Pengaruh Kepemimpinan Transformasional terhadap Keterikatan Kerja melalui Keadilan Organisasional sebagai Variabel Mediasi - Raharjo, Dina Christina; Witiastuti, Rini` Setyo (Universitas Negeri Semarang, 2016)
This study is aimed to know the direct and indirect effect of the transformational leadership, distibutive justice, procedural justice, interactional justice towards nurses’ work engagement which is mediated by distributive justice, procedural justice, and interactional justice. The 117 nurses who worked in the hospitalization section Grade III in RSUD Tugurejo Semarang were the population of the study.The sample of this study was taken by using propotioned random sampling methodology. 91 nurses were taken as the sample of the study. The method of data collection is by questionares which was measured by likert scale. Data analysis using SPSS for Windows version 21. The result of theis study showed transformational leadership have positive effect on distributive justice, procedural justice, and interactional justice. Distributive justice and interactional justice have positive effect on work engagement. Transformational leadership and procedural justice have no effect on work engagement. Distributive justice, procedural justice, and interactional justice was able to mediate the relationship of the transformational leadership towards nurses’ work engagement in hospitalization section Grade III in RSUD Tugurejo Semarang.